Ghana : Fourth Review Under the Poverty Reduction and Growth Facility, Requests for Waiver of Performance Criteria and for Extension of the Commitment Period. (IMF Staff Country Reports; Country Report, 2002)
This paper examines Ghana's Fourth Review Under the Poverty Reduction and Growth Facility and Requests for Waiver of Performance Criteria and for Extension of the Commitment Period. Most end-August 2001 quantitative performance criteria were met, but waivers are requested for nonobservance of two structural performance criteria and the ceilings on short-term official external debt and the stock of arrears in the road sector. The authorities' program for 2002 seeks to consolidate on the macroeconomic gains of 2001, accelerate structural reforms, and create the conditions for faster growth and poverty reduction.